2022
DOI: 10.3390/su142013118
|View full text |Cite
|
Sign up to set email alerts
|

Use of RPA Images in the Mapping of the Chlorophyll Index of Coffee Plants

Abstract: Coffee trading is an important source of income for the Brazilian commercial balance. Chlorophyll (Chl) are pigments responsible for converting radiation into energy; these pigments are closely related to the photosynthetic efficiency of plants, and the evaluation of the nutritional status of the coffee tree. The inversion method can be used for estimating the canopy chlorophyll content (Chlcanopy) using the leaf chlorophyll content (Chlleaf) and the leaf area index (LAI). The application of vegetation indices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Bento et al [58] calculated the height and canopy diameter of newly transplanted coffee plants at three development periods, observed statistical differences between field measurements and aerial images, estimated linear equations between field data and aerial images, and monitored the temporal profile of growth and development of the studied cultivar in the field based on information extracted from aerial images using RPASs, with significant results compared to actual field data. Santos et al [59] aimed to identify which vegetation indices adequately explained plant chlorophyll and evaluated the relationships between vegetation indices obtained from RPAS images and leaf and canopy chlorophyll in coffee plants during the rainy and dry seasons. Also, focusing on chlorophyll estimation in coffee plants, Arteaga-López et al [60] identified the support vector machine model with the best performance and the CVI, GNDVI, and GCI vegetation indices with the best results.…”
Section: Temporal Evolution Of Research and Characteristics Of The St...mentioning
confidence: 99%
“…Bento et al [58] calculated the height and canopy diameter of newly transplanted coffee plants at three development periods, observed statistical differences between field measurements and aerial images, estimated linear equations between field data and aerial images, and monitored the temporal profile of growth and development of the studied cultivar in the field based on information extracted from aerial images using RPASs, with significant results compared to actual field data. Santos et al [59] aimed to identify which vegetation indices adequately explained plant chlorophyll and evaluated the relationships between vegetation indices obtained from RPAS images and leaf and canopy chlorophyll in coffee plants during the rainy and dry seasons. Also, focusing on chlorophyll estimation in coffee plants, Arteaga-López et al [60] identified the support vector machine model with the best performance and the CVI, GNDVI, and GCI vegetation indices with the best results.…”
Section: Temporal Evolution Of Research and Characteristics Of The St...mentioning
confidence: 99%
“…These studies aimed to mitigate challenges and improve the production of this crop in Brazil. RPA with multispectral sensors can fly over coffee plantations and capture high-resolution (in cm) images at different wavelengths, as highlighted in recent studies by Bento et al [9], Santana et al [10] and Santos et al [11] using such technologies for various applications in coffee farming. Such images can be processed to generate vegetation indices (VI), can provide information on the phytosanitary conditions of crops [12], be used to identify frost damage [13] and be used to identify diseases such as rust in coffee trees [14].…”
Section: Introductionmentioning
confidence: 99%